2007
DOI: 10.1093/nar/gkm625
|View full text |Cite
|
Sign up to set email alerts
|

Properties of an unusual DNA primase from an archaeal plasmid

Abstract: Primases are specialized DNA-dependent RNA polymerases that synthesize a short oligoribonucleotide complementary to single-stranded template DNA. In the context of cellular DNA replication, primases are indispensable since DNA polymerases are not able to start DNA polymerization de novo.The primase activity of the replication protein from the archaeal plasmid pRN1 synthesizes a rather unusual mixed primer consisting of a single ribonucleotide at the 5′ end followed by seven deoxynucleotides. Ribonucleotides an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
52
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 28 publications
(55 citation statements)
references
References 29 publications
(36 reference statements)
2
52
1
Order By: Relevance
“…This operon consists of the two co-transcribed genes -orf56 and orf904. Orf904 codes for the replication protein of pRN1 (Lipps et al 2003;Beck and Lipps 2007), whereas ORF56 is involved in plasmid copy number control . It has previously been shown that an interruption of the replication operon abrogates the replication of pRN1 ).…”
Section: Resultsmentioning
confidence: 99%
“…This operon consists of the two co-transcribed genes -orf56 and orf904. Orf904 codes for the replication protein of pRN1 (Lipps et al 2003;Beck and Lipps 2007), whereas ORF56 is involved in plasmid copy number control . It has previously been shown that an interruption of the replication operon abrogates the replication of pRN1 ).…”
Section: Resultsmentioning
confidence: 99%
“…PriSL has also been shown to possess a terminal transferase activity to extend ssDNA substrates. 4,5,47 SsoDnaG is a more robust primase, with the k cat for RNA primer formation being roughly fourfold higher than that for SsoPriSL. Interestingly, the enzymatic performance constants (k cat /K m ) are roughly equal (Table 1).…”
Section: Potential Roles Of Each Primase In Archaeamentioning
confidence: 99%
“…Georg Lipps and colleagues characterized all three conserved replication proteins encoded in pRN1, including the copy number regulation protein CopG (encoded by ORF56) (219), a DNA-binding protein implicated in plasmid maintenance (PlrA) (encoded by ORF80) (154), and a multifunctional replication protein (RepA) (159,(220)(221)(222). They were the first to reveal that both primase and DNA polymerase (Prim/Pol) activities resided in the pRN1 RepA protein and localized the Prim/Pol activities to the N-terminal part of RepA (220,221). They also found that the C-terminal helicase domain is structurally similar to a superfamily 3 helicase, displaying weak helicase activity in vitro (159).…”
Section: Replication Mechanismsmentioning
confidence: 99%